Effect of adding carbon nanotubes on the thermal conductivity of steel fiber-reinforced concrete. (1st October 2019) - Hassanzadeh-Aghdam, Mohammad Kazem; Mahmoodi, Mohammad Javad; Safi, Mohammad
Abstract: A comprehensive analysis is performed to study the effect of adding carbon nanotubes (CNTs) on the thermal conductivity of short steel fiber (SSF)-reinforced concrete. The role of the CNT dispersion and the CNT/concrete interfacial thermal resistance in the SSF/CNT-reinforced concrete thermal conducting behavior is investigated. A good agreement is observed between the model predictions and available experiment. Also, the influences of the SSF aspect ratio, volume fraction and placement type; and the CNT volume fraction, length, diameter and directional behavior on the concrete thermal conductivities are examined. The results reveal that if the CNTs to be uniformly distributed, and the CNT/concrete interface bonding to be perfect, then the concrete effective thermal conductivity is significantly improved. The increasing both volume fraction and length of the CNT leads to the concrete thermal conductivity enhancement too. The CNT diameter and transverse thermal conductivity cannot affect the SSF/CNT-reinforced concrete thermal conducting behavior as well. Highlights: A physics-based hierarchical model is proposed to analyze the thermal conductivity of steel filler/CNT-reinforced concrete. Both of the CNT/matrix interfacial thermal resistance and CNT agglomeration are speculated in the methodology. Adding CNTs within the steel fiber-reinforced concrete can improve the effective thermal conductivities. The maximal thermal conductivity is achieved by forming the interface perfect bonding, and dispersing the CNTs uniformly.